2015
DOI: 10.4314/tjpr.v14i1.17
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Roasting on Fatty Acid Profile of Brown and Yellow Varieties of Flaxseed (<i>Linum usitatissimum </i>L)

Abstract: Purpose: To monitor changes in fatty acid profiles of brown and yellow varieties of flaxseeds in the raw and roasted states using gas chromatography (GC

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 13 publications
(12 reference statements)
4
9
0
1
Order By: Relevance
“…Moreover, after 60‐day storage, the calculated ratios of SFAs:MUFAs:PUFAs were 0.10:0.20:0.70 and 0.11:0.21:0.69 for raw and roasted samples, respectively. Changes in the fatty acid composition of oil after flaxseed thermal treatment were previously reported by Moknatjou et al …”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…Moreover, after 60‐day storage, the calculated ratios of SFAs:MUFAs:PUFAs were 0.10:0.20:0.70 and 0.11:0.21:0.69 for raw and roasted samples, respectively. Changes in the fatty acid composition of oil after flaxseed thermal treatment were previously reported by Moknatjou et al …”
Section: Resultssupporting
confidence: 67%
“…Moreover, after 60-day storage, the calculated ratios of SFAs:MUFAs:PUFAs were 0.10:0.20:0.70 and 0.11:0.21:0.69 for raw and roasted samples, respectively. Changes in the fatty acid composition of oil after flaxseed thermal treatment were previously reported by Moknatjou et al 7 ; they showed that the roasting of flaxseeds (at 350 ∘ C for 10 min) slightly affected their fatty acid composition (PUFA content decreased from 67.3% to 65.4% in raw and roasted seeds, respectively). Morais et al 8 found, however, that the heat treatment of flaxseed flour in air circulation oven (150 ∘ C, 15 min), and then its 30-day storage, did not change the stability of -linolenic acid.…”
Section: Effect Of Thermal Pre-treatment On the Chemical Composition supporting
confidence: 61%
“…The high stability of fatty acids during the thermal treatment could be due to a relatively short time of the roasting process (8 min). Earlier studies showed a slight effect of roasting at 150–350 °C for 10 min (Moknatjou et al, ) or no effect of infrared roasting (Tuncel et al, ) and roasting at 160 °C for 8–24 min (Waszkowiak et al, ) on the fatty acid composition of flaxseed oil. The roasting of other oilseeds, e.g., rapeseed at 140–180 °C for 5–15 min (Siger et al, ) and safflower seeds at 180 °C up to 30 min (Mariod et al, ), also indicated that there was no significant difference between fatty acid profile of oil from roasted seeds and untreated seeds.…”
Section: Resultsmentioning
confidence: 97%
“…These changes in the chemical composition of pre‐treated flaxseeds may have been caused by the elimination of water (Epaminondas et al , ) during roasting or drying (steamed seeds). On the other hand, Moknatjou et al () showed that thermal treatment increased the content of oil extracted from roasted flaxseeds comparing with raw seeds probable by disruption of the structural integrity of flaxseed coat and intracellular lipid storage organelles and increasing oil extractability. A similar phenomenon may also happen upon the thermal treatment of flaxseed in our study.…”
Section: Resultsmentioning
confidence: 99%